Agenesis of the right lung: an unusual presentation - Pallie, W. (1967)
A case of agenesis or aplasia of the right lung, in a cyanosed neonate, exceptionally associated with a `vascular ring' abnormality produced by a right aortic arch, an aberrant left subclavian artery, and a patent ductus arteriosus, is reported. The presence of an abnormal lobe of the liver, projecting together with small gut and a subhepatic caecum into the right hemithorax, caused mediastinal displacement to the left side and produced the illusion of a diaphragmatic hernia, thereby obscuring the correct preoperative diagnosis.